Aplikasi Pemrograman Java untuk Manajemen Pengelolaan STNK di PT BCA Finance Cabang Pondok Indah - Sutarno Sutarno; Kokoy Rokoyah (Teknik Informatika Universitas Pamulang, 2021)
STNK data processing activities at the SAMSAT Office are the subject of this study specifically discussing various obstacles faced in managing STNK extensions. This research activity was conducted to discuss the problems that exist in PT. BCA Finance regarding STNK lending activities by customers when extending STNK. The obstacle for most customers who have busy work, place of residence and long distances is difficult to carry out the STNK renewal process because they have to return to SAMSAT. Certificate from PT. BCA Finance for customers should be able to help extend the STNK. Administration at PT BCA Finance should be easier in managing data. Researchers are trying to design a good system by designing the system it takes the right steps. The design stages are with the help of graphic diagrams such as ERD (Entity Relationship Diagram), normalization, data base structure. This application design answers the old system which still uses the conventional registration system where this system causes several shortcomings in the renewal management system. The results of this study provide solutions to the main problems that exist in PT BCA Finance in managing the STNK renewal process for customers.